PENGARUH PENGALAMAN LAPANGAN INDUSTRI TERHADAP KESIAPAN KERJA MAHASISWA PROGRAM STUDI D4 MANAJEMEN PERHOTELAN ANGKATAN 2015 UNIVERSITAS NEGERI PADANG - Yulita Sari; youmil abrian (Universitas Negeri Padang, 2020)
Based on this research, the writer recommend the lecturer that concerned with internship programe to guide the students with their choice of where to apply the internship programme which is corresponding to their interest and skill, so that they can be more confident of the skill that they have and develop it. The purpose of the research is to analyze the influence of Internship on Work Readiness to the students which is already did the first and the second internship especially for the 2015 class of Hospitality Management in Padang State University. The kind of the research that used is quantitative descriptive and causal associatitive approach to view the influence of Internship (X) on Work Readiness (Y). The population and sample of this research are the students of Hospitality Management class 2015 of Padang State University. The technique of the data analyze that used is descriptive analysis technique by SPSS 16.00 Version. Based on the research , the results are as follows: (1) Internship is in the good category (52,73%) , (2) Work Readiness is in the good category (56,37%), (3) From simple linear resgresion hypothesis the results is F 1.515 with sig. 0,142 < 0,05, so the intership variabel can explain the work readiness significantly, with an R score value as much 0,523. This means that intership had influence on work readiness as much 52,3%, while 47,7% because of another factor. Therefore the result of it is 9,245 with significant level is 0,000<0,05, so there is significant relationship from both variabel. The regression coefficient as much 0,882 with significant value at 0,000<0,05. It is mean that every 1 unit of the internship influence will gain 0,882 unit of work readiness. Based on this research, the writer recommend the lecturer that concerned with internship program to guide the students with their choice of where to apply the internship programme which is corresponding to their interest and skill, so that they can be more confident of the skill that they have and develop it.